Simple truths of leadership 52 ways to be a servant leader and build trust - Blanchard, Kenneth H. (Oakland Berrett-Koehler, 2022)
Leadership legend Ken Blanchard teams up with Randy Conley to share the most essential lessons on servant leadership and building trust from the heart of his leadership model. Effective leadership comes down to implementing everyday, commonsense practices to help organizations thrive-and yet so many leaders are still missing these fundamental principles from their personal and professional lives. Renowned business experts Ken Blanchard and Randy Conley disclose the simple truths about leadership they have gathered over their long and distinguished careers to help bring common sense into common practice. Featuring two sections-servant leadership and building trust-this book is a collection of Blanchard's greatest hits. It is chock-full of profound and memorable (and in some cases counterintuitive) leadership wisdom, such as. Create autonomy through boundaries. People who plan the battle rarely battle the plan. A relationship with no trust is like a cell phone with no internet. All you can do is play games. The most important part of leadership is what happens when you're not there. This book will help readers incorporate these integral practices into their leadership style, build trust through servant leadership, and make a difference in their own life and the lives of those they influence
Includes bibliographical references and index.
Keywords: Leadership